Phylogenetic Position of Centroglossa and Dunstervillea (Ornithocephalus Clade: Oncidiinae: Orchidaceae) Based on Molecular and Morphological Data - Royer, Carla A. [UNESP]; Toscano De Brito, A. L.V.; Mauad, Anna V. S. R.; Smidt, Eric C. [UNESP] (American Society of Plant Taxonomists, 2022)
Even though the monophyly of the Ornithocephalus clade (Oncidiinae) is currently well defined, the systematic positioning of Centroglossa and Dunstervillea remains obscure in the clade due to the absence in previous phylogenetic studies. Centroglossa has a very similar habit and is indistinguishable from Zygostates, whereas Dunstervillea has as its main characteristic the calcarate labellum, also found in Centroglossa. We clarify the systematic and phylogenetic positioning of Centroglossa and Dunstervillea in the Ornithocephalus clade (OC) through analysis of maximum likelihood, Bayesian inference, and maximum parsimony from molecular data (nrITS and matK cpDNA) and morphology. Our results indicate that Dunstervillea is phylogenetically close to Eloyella; both genera have a psigmoid habit, single-sided and flattened leaves, floral perianth with the same coloring, petals with entire margins, and a short rostellum. Centroglossa appears as a subclade within Zygostates. In addition to several homoplastic features, these two genera have the dorsal position of viscidium as a synapomorphy. The calcarate labellum, common to Centroglossa and Dunstervillea, originated more than once in the OC. Based on the phylogenetic results, we propose the nomenclatural changes to include Dunstervillea in Eloyella and Centroglossa in Zygostates. New synonyms are indicated to Zygostates greeniana and Z. nunes-limae and lectotypes are indicated to Centroglossa macroceras and C. glaziovii.
Keywords: Character encoding; matK; Neotropic; nrITS; synapomorphy